On-going European integration will affect the position of the regions: An analysis of the process and some possible scenarios for the future - Hendrik Vos (European Regional Science Association (ERSA), 1998)
Centrifugal pressures and the ?technical needs of the modern state? (Keating) resulted in demands for decentralisation from the seventies on. Nowadays, regional self-government exists in many EU member-states. This has strengthened the position of the regions, not only within the member-states, but even within the EU itself. Some of the elements that play a role are: [1] The dynamics of European integration resulted in a significant increase in competences for the EC, especially after the Single European Act. However, it appears that most of the integration at the European level occured in those domains which had already been transferred to a regional authority in several member-states. As a result, regions play an increasingly important role in the implementation of EU-regulations which makes them want to have a say in how these are formed. A clear understanding of this evolution makes it possible to interpret some existing theories on integration from a different angle. [2] The EMU will enhance cross-border cooperation between regions. Regional cooperation (at present already visible) will strengthen the evolution as described above. Regions will propose their policies more on their own, apart from the traditional states. [3] The European regional policy has become increasingly important, with the structural funds as main instruments. Attention will be paid to this policy, especially in the light of the expansion of the EU to the east and the reforms that come with this (cfr. Agenda 2000). Primarily, regions will claim a more decisive participation in the regional policy-making. Secundarily, the entry of new member-states implies an expansion of the amount of regions. Typical for the applicant-members from Eastern Europe is that regionalism has a strong appeal in these countries and is on the rise the past few years. [4] Regions found their claims for an increased influence upon the EU-treaty which stipulates that ?decisions should be taken as closely as possible to the citizen?. This paper stresses the regions use of the principle as an argument for increased influence. As integration advances, regions will graduallly become more autonomous partners in the European project. This paper focuses on the determinants of this process and the challenges that will come together with future developments. One argument that will be developped is the unlikeliness that this evolution will lead to a ?Europe of the Regions?, in which regions will totally replace the traditional states. Instead, a ?Europe of the Regions? as described by A. Heywood, ?meaning that regional institutions and groups have increasingly sought direct access to EU bodies, thereby bypassing national governments?, seems more appropriate, because it is less radical. Finally, the paper deals with the crucial problem of institutional settings that will be needed to formalize the role of the regions. The paper critically examines the present alternatives for the Committee of the Regions. Arguments for the unsolved problems (e.g. relationship between local and regional representatives) will be presented. No matter which form this new institutional setting takes (an adjusted CoR or a new body), it will have to take these arguments into consideration. theme B
Keywords: 330